Brachysomus (Hippomias) samos sp. n. from Greece—first island endemism in the genus (Coleoptera: Curculionidae: Entiminae) - Yunakov, Nikolai; Germann, Christoph (Zootaxa, 2012)
Brachysomus (Hippomias) samos sp. n. is described from the Oros Ambelos mountains on Samos Island (Greece). Thehygrophilous and detritivorous new species is endemic to a very restricted area. Brachysomus samos is close to B. pelexYunakov, 2006, B. moczarskii Penecke, 1924 and B. armatus Yunakov, 2006 based on characteristics of the median lobeof the aedeagus, and on the conspicuously long apodemes. Brachysomus samos furthermore strongly resembles B. armatus and B. curvimanus Yunakov, 2006 in the characteristic shape of the head capsule and epifrons.